European Association for the Study of the Liver (EASL), European Association for the Study of Diabetes (EASD) and European Association for the Study of Obesity (EASO) clinical practice recommendations for the management of non‐alcoholic fatty liver disease: evaluation of their application in people with Type 2 diabetes. Issue 3 (10th January 2018) - Sberna, A. L.; Bouillet, B.; Rouland, A.; Brindisi, M. C.; Nguyen, A.; Mouillot, T.; Duvillard, L.; Denimal, D.; Loffroy, R.; Vergès, B.; Hillon, P.; Petit, J. M.
Abstract: Aims: To evaluate the application of the recently proposed recommendations by the European Association for the Study of the Liver, European Association for the Study of Diabetes and European Association for the Study of Obesity for the diagnosis, treatment and follow‐up of non‐alcoholic fatty liver disease in people with Type 2 diabetes. Methods: A total of 179 people with Type 2 diabetes were included in this study. Liver fat content (assessed using proton magnetic resonance spectroscopy), fatty liver index score, non‐alcoholic fatty liver disease fibrosis score, and SteatoTest and FibroTest scores were determined. Results: According to proton magnetic resonance spectroscopy, 68.7% of participants had steatosis (liver fat content >5.5%). The application of the guidelines using several combinations (fatty liver index + non‐alcoholic fatty liver disease fibrosis scores, Steatotest + FibroTest scores, proton magnetic resonance spectroscopy + non‐alcoholic fatty liver disease fibrosis score, proton magnetic resonance spectroscopy + FibroTest) resulted in a referral to a liver clinic for 33.5–84.9% people with Type 2 diabetes. Conclusions: The application of these new algorithms for the diagnosis, and follow‐up of non‐alcoholic fatty liver disease would lead to an excessive number of people with Type 2 diabetes being referred to a liver clinic. We suggest that new clinical and/or biological biomarkers of steatosis and fibrosis be specifically validated in people with Type 2 diabetes. What's new?: Non‐alcoholic fatty liver disease (NAFLD) is very common in people with Type 2 diabetes mellitus. The European Association for the Study of the Liver (EASL), European Association for the Study of Diabetes (EASD) and European Association for the Study of Obesity (EASO) recently proposed recommendations for the diagnosis, treatment and follow‐up of NAFLD. We evaluated the application of these new EASL‐EASD‐EASO recommendations for the diagnosis of NAFLD in people with Type 2 diabetes. Application of these new algorithms would lead to an excessive number of people with Type 2 diabetes being referred to a liver clinic.